The Enigmatic Statuette of Djehutymose (MFA 24.743): Deputy of Wawat and Viceroy of Kush - Klotz, David.
During excavations at the temple of Taharqa at Semna, George Reisner discovered an exceptional New Kingdom private statuette covered with short cryptographic inscriptions. The peculiar texts on this statuette, now in the collection at the Museum of Fine Arts in Boston (MFA 24.743), received a preliminary treatment by Étienne Drioton in the extensive catalogue of the Semna excavations by D. Dunham and J. Janssen (1960).Nevertheless, this object has otherwise garnered little scholarly attention.A new translation of the enigmatic texts raises important considerations for understanding both the function of cryptography in private statuary and the evolution of viceregal authority in the Eighteenth Dynasty. The texts reveal that the statue belonged to a high ofcial from the Egyptian administration in Nubia, the idnw n WAwA.t (deputy viceroy of Wawat), Djehutymose. Several stylistic features of the statuette suggest a date to the reign of Amenhotep III, when Djehutymose would have been deputy to the viceroy Merymose; this administrative relationship nds additional support from a previously overlooked rock inscription in the Wadi Allaqi. This article contends that the idnw n WAwA.t Djehutymose should be identied with the viceroy of the same name dating to the reign of Akhenaten. Representing the earliest-known attestation of the division of the deputy viceroy position into two geographically dened ofces, this small statuette provides insight into hitherto little known aspects of viceregal succession and the evolution of the dual deputy ofces.